Analisis Kelayakan Usaha Pangkalan Gas LPG Tri Putra Kota Parepare - Luthfi, Muhammad; Nurfadhilah (Institut Agama Islam Negeri Parepare, 2022)
This research aims to evaluate the feasibility of a trading business, especially in the case of the Tri Putra 3Kg LPG Gas Base Business. The research method used is descriptive qualitative by utilizing primary and secondary data. Primary data was obtained through direct research and interviews with respondents, while secondary data was obtained from various sources such as journals and books. The data analysis process follows the stages of data reduction, data presentation (data display), and conclusion drawing/verification. The data analysis method is based on the concept of Miles and Huberman, which organizes data collection activities in three main stages, namely data reduction, data presentation, and verification and conclusion drawing. The results showed that Tri Putra's 3Kg LPG Gas Base Business is feasible. This feasibility is proven through the fulfillment of relevant business aspects and the ability to apply the 4P concept (Product, Price, Place, and Promotion) well. These findings can be a valuable consideration for those who wish to start a similar venture, making a positive contribution to business development in this industry.